2015
DOI: 10.14440/bladder.2015.39
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in overall and urothelial carcinoma specific mortality associated with healthcare insurance status

Abstract: OBJECTIVE:We investigated the association of insurance status with urothelial carcinoma (UC) mortality outcomes to further understand the relationship of socioeconomic status (SES) and UC disease outcomes. MATERIALS AND METHODS:We performed an IRB approved, retrospective review of patients newly diagnosed with bladder UC in the years 2004 and 2005. Data were collected from January 2004 to September 2014 regarding insurance, demographics, operations, surgical pathology, and follow-up care. Insurance was charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…A strong correlation between socioeconomic status and survival of patients with bladder cancer has been observed in other studies. In other words, the increase in premature death was seen in patients with low socioeconomic status than those with higher socioeconomic status (Siddiqui et al, 2015). The patients with low socio-economic status experience lower survival due to reduced access to health care, biology of the disease, environmental factors, exposure to tobacco, and health habits (Shackley and Clarke, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A strong correlation between socioeconomic status and survival of patients with bladder cancer has been observed in other studies. In other words, the increase in premature death was seen in patients with low socioeconomic status than those with higher socioeconomic status (Siddiqui et al, 2015). The patients with low socio-economic status experience lower survival due to reduced access to health care, biology of the disease, environmental factors, exposure to tobacco, and health habits (Shackley and Clarke, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…17 While treatment methods may be guided by physicians, patient adherence with future appointments more closely reflects individual patient factors and SDOH. [18][19][20][21][22][23] Adherence is likely significantly associated with an individual's ability to access care, highlighting institutional and community disparities. Our results indicate adherence outcomes are significantly associated with a patient's SES based on income and ADI, even after controlling for race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research on SDOH has demonstrated that patients with higher SDOH needs have decreased illness prevention and disease management, while also having higher rates of no-shows and emergency room utilization. [18][19][20][21][22][23] In fact, a systematic review of pediatric weight-management programs found that Black participants had higher dropout rates, and low family income was associated with decreased adherence with management protocols. 24 Our work demonstrates that similar disparities exist for patients undergoing renal mass management.…”
Section: Discussionmentioning
confidence: 99%
“…4–6 Within urology specifically, worsened outcomes due to socioeconomic disadvantages have been documented in the context of bladder cancer, prostate cancer, kidney cancer and stone disease, to name a few. 7–10…”
Section: Introductionmentioning
confidence: 99%